Overexpression of Heme Oxygenase-1 in Mesenchymal Stem Cells Augments Their Protection on Retinal Cells In Vitro and Attenuates Retinal Ischemia/Reperfusion Injury In Vivo against Oxidative Stress - Li Li; GaiPing Du; DaJiang Wang; Jin Zhou; Guomin Jiang; Hua Jiang (Stem Cells International)
Retinal ischemia/reperfusion (I/R) injury, involving several ocular diseases, seriously threatens human ocular health, mainly treated by attenuating I/R-induced oxidative stress. Currently, mesenchymal stem cells (MSCs) could restore I/R-injured retina through paracrine secretion. Additionally, heme oxygenase-1 (HO-1) could ameliorate oxidative stress and thus retinal apoptosis, but the expression of HO-1 in MSC is limited. Here, we hypothesized that overexpression of HO-1 in MSC (MSC-HO-1) may significantly improve their retina-protective potentials. The overexpression of HO-1 in MSC was achieved by lentivirus transduction. Then, MSC or MSC-HO-1 was cocultured with retinal ganglion cells (RGC-5) in H2O2-simulated oxidative condition and their protection on RGC-5 was systemically valuated in vitro. Compared with MSC, MSC-HO-1 significantly attenuated H2O2-induced injury of RGC-5, including decrease in cellular ROS level and apoptosis, activation of antiapoptotic proteins p-Akt and Bcl-2, and blockage of proapoptotic proteins cleaved caspase 3 and Bax. In retinal I/R rats model, compared with control MSC, MSC-HO-1-treated retina significantly retrieved its structural thickness, reduced cell apoptosis, markedly attenuated retinal oxidative stress level, and largely regained the activities of typical antioxidant enzymes, SOD and CAT. Therefore, it could be concluded that overexpression of HO-1 provides a promising strategy to enhance the MSC-based therapy for I/R-related retinal injury.